Pre-Filtering Techniques for Spectrum Narrowing Caused by Optical Node Traversal in Ultra-Dense WDM Networks - Kazuya Okamura; Yojiro Mori; Hiroshi Hasegawa (IEEE Photonics Journal)
To improve the spectral efficiency and increase network capacity, wavelength signals must be multiplexed densely, i.e., ultra-dense wavelength-division-multiplexing (WDM) networks. However, the spectrum of each WDM signal is narrowed by the wavelength-selective switches placed in optical nodes, so the transmissible distance and node hop count of the signal are strictly limited. To counter this spectrum narrowing problem caused by optical node traversal in ultra-dense WDM networks, pre-filtering techniques have been proposed. This paper comprehensively investigates the performance of four pre-filtering techniques: conventional Nyquist filtering, pre-emphasis filtering, partial-response filtering, and the combination of pre-emphasis and partial-response filtering. We conduct extensive computer simulations and discuss the optimality of pre-filtering techniques. The simulation results show that the adaptive use of pre-filtering can substantially extend the maximum attainable transmission distance and hop counts of 4/16/64-QAM signals.